Investasi dan Inflasi Sebagai Instrumen Pertumbuhan Ekonomi di Indonesia dalam Perspektif Ekonomi Islam - Sherly Puspa Dewi; Muhammad Iqbal Fasa; Suharto (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2021)
Economic growth can be interpreted as one of the important indicators to describe the progress of a country financially or prosperously. High economic growth and not accompanied by improvements in a solid economic structure can lead to domestic economic instability and high inflation rates. Investment has an important role in economic growth, namely creating income. The types of methods used in this research are qualitative research methods and library research. Data collection in this study uses content analysis techniques and the data source used is secondary data. Inflation that occurred in Indonesia in 2015-2020 was still at a mild level so that an increase in inflation still had a positive effect. In this study, investment also has a positive effect. Investment in Islam which aims to improve people's welfare and create a society with a decent standard of living and reduce the poverty line.